A Study of Ferdinand de Saussure's Semiotics in the Film Jilbab Traveler: Love Sparks in Korea by Asma Nadia - Andi Febiyola. M; Yusmah; Nurlaelah; Kamal (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to describe the relationship between the form of the signifier and signified and to interpret the signs found in each scene and dialogue in the film Jilbab Traveler: Love Sparks in Korea by Asma Nadia using Ferdinand de Saussure’s semiotic theory. This research employs a descriptive qualitative approach. The data collection techniques used are repeated observation, note-taking, and documentation by capturing several images from scenes in the film and analyzing the meanings contained within them. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The results of the study show that there are 31 scene and dialogue data containing signs in the film. A total of 148 data consisting of signifiers and signifieds were identified, involving Indonesian, English, and Korean languages. The findings indicate that the relationship between signifiers and signifieds, as well as the dialogues in the film Jilbab Traveler: Love Sparks in Korea by Asma Nadia, does not merely function to construct the storyline but also represents moral, social, religious, and cultural values. Therefore, this film contains various symbolic meanings that reflect the identity of Muslim women, cultural interactions, and religious values in a global context.